1973
DOI: 10.3382/ps.0520452
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Effect of Oral Ingestion of Methyl Mercury on Chicks and Rats

Abstract: 1968a. Limiting essential amino acids in soybean meal for growing chickens and the effect of heat upon the availability of the essential amino acids. Poultry Sci. ABSTRACTTwo experiments with day-old chicks and one experiment with weanling rats were conducted to determine: (1) whether low levels of mercury found in some feedstuffs would result in hazardous accumulations of mercury in their tissues, and (2) the effects of feeding various dietary levels of methyl mercury to chicks and rats. Data show that feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The detected amount of it was 1.86±0.51 mg/kg in great tits (Parus major) in Belgium (Janssens et al, 2002), 0.66± 0.68 mg/kg in rural area and 1.09±0.40 in forest habitat in passerines in Portugal (Costa et al 2011) and 383 μg/kg in cattle egret (Bubulcus ibis) in Bali (Burger and Gochfeld 1997). Also, it has been found that young chickens can tolerate 1.35 mg/kg diet (March et al 1983), but 5 mg/kg increases mortality (Soares 1973). Bhatnagar et al (1982) examined that 0.5 mg Hg/kg diet as methylmercury has no effect on behavioural endpoints in ducks, although 3.8 mg/kg had adverse effects.…”
Section: Mercurymentioning
confidence: 98%
“…The detected amount of it was 1.86±0.51 mg/kg in great tits (Parus major) in Belgium (Janssens et al, 2002), 0.66± 0.68 mg/kg in rural area and 1.09±0.40 in forest habitat in passerines in Portugal (Costa et al 2011) and 383 μg/kg in cattle egret (Bubulcus ibis) in Bali (Burger and Gochfeld 1997). Also, it has been found that young chickens can tolerate 1.35 mg/kg diet (March et al 1983), but 5 mg/kg increases mortality (Soares 1973). Bhatnagar et al (1982) examined that 0.5 mg Hg/kg diet as methylmercury has no effect on behavioural endpoints in ducks, although 3.8 mg/kg had adverse effects.…”
Section: Mercurymentioning
confidence: 98%
“…Negative effects on the neurological (Chang, 1977;Burbacher et al, 1990;Nagashima, 1997) and immune systems (Ilback, 1991;Ilback et al, 1996) and other tissues (SnelgroveHobson et al, 1988) are well documented in humans and captive mammals. Effects of methylmercury exposure have been reported in captive birds (Borg et al, 1970;Fimreite and Karstad, 1971;Soares et al, 1973;Pass et al, 1975;Hughes et al, 1976;Heinz and Hoffman, 1998;Hoffman and Heinz, 1998), including trans-generational effects (Heinz, 1975(Heinz, , 1976(Heinz, , 1979. These studies have focused on non-piscivorous species, whereas the top predators in aquatic systems are often piscivorous mammals and birds.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory mammals tended to show the greatest concentration of CH 3 HgCl in liver and kidney, with brain and muscle tissue also accumu lating appreciable quantities (136)(137)(138)(139)(140). Oysters (Crassostrea virginica) concentrated this compound predominantly in the gills (141).…”
Section: B Biological Distributionmentioning
confidence: 99%